The evaluation and treatment of nocturia: a consensus statement - Weiss, Jeffrey P.; Blaivas, Jerry G.; Bliwise, Donald L.; Dmochowski, Roger R.; DuBeau, Catherine E.; Lowe, Franklin C.; Petrou, Steven P.; Van Kerrebroeck, Philip E.V.; Rosen, Raymond C.; Wein, Alan J. (BJU international, 2011)
What’s known on the subject? and What does the study add? Nocturia is currently defined by the International Continence Society (ICS) as the complaint that an individual has to wake at night one or more times to void. It is, however, an underreported, understudied, and infrequently recognized problem in adults. Many factors may contribute to nocturia which are treatable, yet patients do not seek care or the condition may not be identified by providers. This paper aims to help healthcare providers better serve patients who are experiencing nocturia by summarizing current research, clinical approaches, and treatment options. The results of the conference provide a balanced evaluation of the full treatment armamentarium capable of meeting the needs of patients with the manifold causes of nocturia such as nocturnal polyuria, overactive bladder, or benign prostatic hyperplasia.